Reference values and associated factors for Japanese newborns' blood pressure and pulse rate: the babies' and their parents' longitudinal observation in Suzuki Memorial Hospital on intrauterine period (BOSHI) study. Issue 8 (August 2016) - Satoh, Michihiro; Inoue, Ryusuke; Tada, Hideko; Hosaka, Miki; Metoki, Hirohito; Asayama, Kei; Murakami, Takahisa; Mano, Nariyasu; Ohkubo, Takayoshi; Yagihashi, Katsuyo; Hoshi, Kazuhiko; Suzuki, Masakuni; et al.
Abstract : Objective: Currently, normative means and ranges of blood pressure (BP) and pulse rates in Japanese newborns are not available. The objective of the present study was to estimate BP, pulse rate, and their distribution among Japanese newborns. Methods: Using oscillometric devices, arm or calf BP and pulse rate levels were obtained from 3148 infants born between 2007 and 2014, consecutively at Suzuki Memorial Hospital, Iwanuma, Japan. Of those, data from 2628 full-term, singleton newborns with BP measured on day 3 after birth were analyzed. Results: Arm SBP/DBP and pulse rate in the reference group ( n  = 2628) were 70.5 ± 7.4/44.3 ± 6.7 mmHg and 117.3 ± 16.6 bpm, respectively. The 5–95th percentiles were 58–83 mmHg for SBP, 35–57 mmHg for DBP, and 91–145 bpm for pulse rate. Similar values were obtained from calf measurements. In multiple regression analysis, birth weight and spontaneous cephalic delivery were positively and light/deep sleep was inversely associated with higher arm SBP/DBP ( P  ⩽ 0.04), whereas sex, Apgar score, gestational age, and mother's age did not significantly affect BP levels ( P  ≥ 0.06). Male sex, gestational age, spontaneous cephalic delivery, and light/deep sleep were inversely associated with higher pulse rate ( P  ⩽ 0.02). Conclusion: The present study is the first to show the distributions of Asian newborns' BP levels and pulse rate. The assessment of newborns' BP levels and pulse rate should consider birth weight, gestational age after birth, and actual condition at BP measurement. Abstract : Supplemental Digital Content is available in the text